Interweaving Autonomous Learning and Peer-tutoring in Coaching EFL Student-Teachers - Aleida Ariza Ariza; John Jairo Viáfara González (Profile: Issues in Teachers' Professional Development)
In this article we share the findings on the exploration of undergraduate efl (English as a Foreign Language) student-teachers' professional preparation and autonomous practices. Participants were tutees who attended tutorial sessions with peers in higher semesters. In this context, tutoring was based on a model we designed. As the model was implemented, they collected information by means of multiple qualitative research instruments. Results indicate that tutees' learning process was strongly influenced by their personality and attitudes. Similarly, tutees expanded their views in regard to the English language, its learning, and their communicative competence. Finally, we pinpoint some considerations for others interested in adopting this pedagogical strategy.